2020
DOI: 10.1002/adbi.202000157
|View full text |Cite
|
Sign up to set email alerts
|

Nanochannel‐Based Poration Drives Benign and Effective Nonviral Gene Delivery to Peripheral Nerve Tissue

Abstract: While gene and cell therapies have emerged as promising treatment strategies for various neurological conditions, heavy reliance on viral vectors can hamper widespread clinical implementation. Here, the use of tissue nanotransfection as a platform nanotechnology to drive nonviral gene delivery to nerve tissue via nanochannels, in an effective, controlled, and benign manner is explored. TNT facilitates plasmid DNA delivery to the sciatic nerve of mice in a voltage‐dependent manner. Compared to standard bulk ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…TNT is used to treat ischemic stroke in mice by delivering reprogramming factors (Etv2, Foxc2, and Fli1 (EFF)) which are vasculogenic cell therapies. These treatment methods lead to increased vascularity and revealed infract resolution, indicating that TNT is a particularly promising future approach to treat ischemic stroke [10].…”
Section: Discussionmentioning
confidence: 99%
“…TNT is used to treat ischemic stroke in mice by delivering reprogramming factors (Etv2, Foxc2, and Fli1 (EFF)) which are vasculogenic cell therapies. These treatment methods lead to increased vascularity and revealed infract resolution, indicating that TNT is a particularly promising future approach to treat ischemic stroke [10].…”
Section: Discussionmentioning
confidence: 99%
“…Nonviral approaches to gene/cargo delivery have the potential to facilitate the development of highly translational cell therapies for a wide variety of conditions ( 18 , 19 , 41 45 ). Here, we showed that nonviral nanotransfection of Etv2 , Foxc2 , and Fli1 ( EFF ) into fibroblasts can drive reprogramming-based vasculogenic cell therapies of relevance to ischemic stroke when deployed intracranially.…”
Section: Discussionmentioning
confidence: 99%
“…TNT can be used to deliver reprogramming factors genes Etv2, Foxc2, and Fli1 (EFF) to crushed nerves, which results in increased vascularity and better recovery. Tissue Nano transfection, when compared to Bulk Electroporation (BEP), does not hinder toe-spread and pinprick response and does not affect electrophysiological parameters, whereas BEP can cause nerve damage and increase macrophage overexpression (10).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%